Anaplastic Lymphoma Kinase–Positive Large B-Cell Lymphoma: Description of a Case With an Unexpected Clinical Outcome. (February 2015) - Zanelli, Magda; Valli, Riccardo; Capodanno, Isabella; Ragazzi, Moira; Ascani, Stefano
Anaplastic lymphoma kinase–positive (ALK-positive) large B-cell lymphoma is a rare and aggressive variant of large B-cell lymphoma (LBCL), first reported by Delsol et al in 1997, showing distinctive morphologic, immunophenotypic and cytogenetic features. The latest 2008 World Health Organization Classification of Tumours of Haematopoietic and Lymphoid tissues recognizes ALK-positive LBCL as a separate entity. Here, we report a case of ALK-positive large B-cell lymphoma in a 53-year-old man with diffuse abdominal and mediastinal lymph-nodes involvement. According to the Ann Arbor staging system, the patient had a stage IIIB lymphoma. The age-adjusted International Prognostic Index was 2 (stage III and elevated lactate dehydrogenase), so the disease was considered high risk. The patient underwent chemotherapy, radiotherapy, and an autologous stem cell transplantation. The patient is alive and free of disease 35 months after diagnosis.